(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the influence of gender stereotypes on the process of adolescent personality formation based on modern psychological theories. The study examines the impact of traditional perspectives formed within the family, educational institutions, and media environments on adolescents’ self-esteem and career choices. The article concludes with scientific recommendations for creating a psychological environment free from gender constraints to expand the “ zone of proximal development” of the individual.